PA28γ, an Accomplice to Malignant Cancer - Lei, Kexin; Bai, Hetian; Sun, Silu; Xin, Chuan; Li, Jing; Chen, Qianming (Frontiers in Oncology, 2020)
PA28γ is a nuclear activator of the 20S proteasome, which is involved in the regulation of several essential cellular processes and angiogenesis. Over the past 20 years, many amino acid sites and motifs have been proven to play important roles in the characteristic functions of PA28γ. The number of binding partners and validated cellular functions of PA28γ have increased, which has facilitated the clarification of its involvement in different biological events. PA28γ is involved in the progression of various diseases, and its aberrant overexpression in cancer is remarkable. Patients with low levels of PA28γ expression have a higher survival rate than those with high levels of PA28γ expression, as has been shown for a wide variety of tumors. The functions of PA28γ in cancer can be divided into five main categories: cell proliferation, cell apoptosis, metastasis and invasion, cell nuclear dynamics that have relevance to angiogenesis, and viral infection. In this review, we focus on the role of PA28γ in cancer, summarizing its aberrant expression, prooncogenic effects and underlying mechanisms in various cancers, and we highlight the possible cancer-related applications of PA28γ, such as its potential use in the diagnosis, targeted treatment and prognostic assessment of cancer.